Astigmatism in post-operative cataract patients (1994)
The aim of the study was to find out the various degrees of post-operative refractive astigmatism in our cataract patients, causes of the astigmatism and ways of minimising this problem. The total number of post-operative refractive astigmatism was determined in patients following cataract surgery. 22% of the patients had an astigmatism of greater than 2 diopters although only 1.9% had the more intolerable astigmatism of greater than 4 diopters. Associated causes for the astigmatism included intraoperative vitreous loss, wound dehiscence, pterygium and corneal scars. With the advent of microsurgery and better magnification, suggestions are made as to how to minimise this condition which, if high proves very intolerable for the patient.